2020
DOI: 10.1007/s40843-020-1462-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase degradation of all-inorganic perovskite CsPbI2Br films induced by a p-type CuI granular capping layer

Abstract: It is necessary to evaluate the interactions between the different functional layers in optoelectronic devices to optimize device performance. Recently, the I-rich allinorganic perovskite CsPbI 2 Br has attracted tremendous attention for use in solar cell applications because of its suitable band gap and favorable photo and thermal stabilities. It has been reported that the undesirable phase degradation of the photoactive α phase CsPbI 2 Br to the non-perovskite δ phase could be triggered by high humidity. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…There are differences of thermal reactions of Cu used as a Cu element itself or in Cu compounds such as CuI and CuSCN. Several studies showed that the decomposition of Cu compounds after thermal annealing can result in the formation of impurities such as PbI 2 . , This is particularly important as solar cell operating temperatures in the field can reach beyond 65 °C, and processing steps such as cell encapsulation would require even higher temperature thresholds . Therefore, it is significantly important to understand the degradation mechanisms arising from Cu interactions with the perovskite layer at the elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…There are differences of thermal reactions of Cu used as a Cu element itself or in Cu compounds such as CuI and CuSCN. Several studies showed that the decomposition of Cu compounds after thermal annealing can result in the formation of impurities such as PbI 2 . , This is particularly important as solar cell operating temperatures in the field can reach beyond 65 °C, and processing steps such as cell encapsulation would require even higher temperature thresholds . Therefore, it is significantly important to understand the degradation mechanisms arising from Cu interactions with the perovskite layer at the elevated temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Organic-inorganic lead halide perovskite solar cells (PSCs) have been instrumental in converting solar energy into electricity at low cost, and their efficiency has increased from 3.8% to 25.5% [1][2][3][4][5][6][7][8]. Improvements in their overall stability have also contributed to lead-based perovskite's success [9][10][11][12][13][14][15][16]; nonetheless, the toxicity of lead remains a concern in the large-scale application of PSCs, and the potential danger of lead poisoning has cast doubts over their future implementation [17,18]. Recently, tin PSCs (TPSCs), which are more environmentally friendly, have become the most promising candidates for lead-free PSCs [19][20][21][22]; however, poor crystallinity and the oxidation of Sn 2+ to Sn 4+ in tin perovskite films remain barriers to their use in efficient and stable solar cells [23].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with organic metal halide perovskites, all-inorganic halide perovskites, CsPbX 3 (X = I, Br, and Cl), have enhanced compositional, thermal, and optical stability, especially CsPbBr 3 , which, meanwhile, shows excellent stability against humidity. Direct band gap CsPbBr 3 , with a corner-shared [PbBr 6 ] 4– octahedron in a 3D framework, has large absorption cross-sections and superior optoelectrical properties . Recently, it has been widely applied in solar cells, light-emitting diodes, photodetectors, lasers, , and so on. , …”
Section: Introductionmentioning
confidence: 99%